RANCANG BANGUN MESIN PENGUPAS KULIT BAWANG MERAH - Shafira Nindhia Fira; Anugerah Putra R; Bayu Prasetya; Husman Husman; Adhe Anggry (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
In the Sungailiat area, there are many SME (small and medium enterprises) culinary types, one of which is processed fried onions. Yuliana's mother is the owner of a fried onion business called